2021
DOI: 10.1016/j.ajoc.2021.101143
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of a glaucomatous optic disc pit

Abstract: Purpose To report a patient in whom a glaucomatous optic disc pit (ODP) disappeared spontaneously. Observations A 59-year-old Korean woman presented with primary open-angle glaucoma, an ODP, and deep superior cecocentral scotomas. She was treated with topical ocular hypotensive medications and followed. Twenty-eight months later, the superior cecocentral scotomas were not detectable with repeated visual field testing. With repeated optical coherence tomography (OCT), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…23,24 Thus, in contrast to the congenital ODPM, the primary treatment objective for an eye with glaucomatous ODPM would be to primarily prevent the intraocular pressure fluctuations. 10,12,25 In this study, we observed one eye in which maculopathy signs resolved completely following trabeculectomy surgery alone. The demographic, clinical, and OCT characteristics of congenital and acquired ODPM may serve as a guide when considering intervention in such cases, giving the current study clinical significance.…”
Section: Discussionmentioning
confidence: 67%
“…23,24 Thus, in contrast to the congenital ODPM, the primary treatment objective for an eye with glaucomatous ODPM would be to primarily prevent the intraocular pressure fluctuations. 10,12,25 In this study, we observed one eye in which maculopathy signs resolved completely following trabeculectomy surgery alone. The demographic, clinical, and OCT characteristics of congenital and acquired ODPM may serve as a guide when considering intervention in such cases, giving the current study clinical significance.…”
Section: Discussionmentioning
confidence: 67%
“…A known complication of an ODP is maculopathy. It has been reported that an optic disc pit can resolve after starting ocular hypotensive medicationand that ODP maculopathy may resolve spontaneous or after posterior vitreous detachment [1,2]. however, this case is the first to show a reversal of glaucomatous ODP associated maculopathy after topical ocular hypotensive medication, more specifically, a prostaglandin analog.…”
Section: Discussionmentioning
confidence: 68%
“…An optic disc pit (ODP) can be acquired as a result of localized glaucomatous damage [1]. A known complication of an ODP is maculopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Following ocular hypotensive treatment, Kim et al reported the reversal of a glaucomatous optic disc pit without maculopathy. 6 Maculopathy in an optic disc pit is usually accompanied by retinoschisis and/or serous macular detachment and retinal pigment epithelial changes. 7 Surgical intervention in the form of pars plana vitrectomy with internal limiting membrane peeling and gas endotamponade is frequently the treatment of choice for cases of maculopathy caused by an optic disc pit.…”
Section: Introductionmentioning
confidence: 99%